Orthodontic treatment and referral patterns: A survey of pediatric dentists, general practitioners, and orthodontists - Abdullah M. Aldrees; Nada E. Tashkandi; Areej A. AlWanis; Munerah S. AlSanouni; Nasir H. Al-Hamlan (Saudi Dental Journal)
Objective: This study aims to assess the orthodontic diagnostic skills, referral patterns, and the perceptions of orthodontic benefits of pediatric and general dentists in comparison with orthodontists. Materials and methods: Two online surveys were e-mailed to pediatric dentists, general dentistry practitioners, and orthodontists registered as members of the Saudi Dental Society and the Saudi Orthodontic Society. The surveys included questions about the type of orthodontic treatment provided, referral trends, and timing; presumed benefits associated with successful orthodontic treatment; and diagnosis and treatment plans of seven cases representing different malocclusions. Results: In total, 25 orthodontists, 18 pediatric dentists, and 14 general practitioners completed the survey. Only 38.8% of pediatric dentists and 7.1% of general practitioners reported that they practiced orthodontics clinically. The perceptions of the three groups toward the benefits of orthodontic treatment were comparable in the psychosocial areas. However, the orthodontists perceived significantly lesser effects of orthodontic treatment on the amelioration of temporomandibular disorder (TMD) symptoms. Pediatric dentists tended to rate the need and urgency of treatment higher, while general practitioners tended to rate the need of treatment lower. The selected treatment plans for three early malocclusion cases showed the greatest discrepancies between the orthodontists and the other two groups. Conclusions: The orthodontists consistently and significantly downplayed the perceived benefit of orthodontic treatment to reduce TMD symptoms. Also, while there was a similarity in the diagnosis, there were notable differences in the proposed treatment approaches, perceived treatment need, and timing of intervention between the three groups of practitioners. Keywords: Orthodontist, Pediatric dentist, General practitioners, Perception, Knowledge